2019 28th IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2019
DOI: 10.1109/ro-man46459.2019.8956367
|View full text |Cite
|
Sign up to set email alerts
|

Influencing Hand-washing Behaviour With a Social Robot: HRI Study With School Children in Rural India

Abstract: The work presented in this paper reports the influence of a social robot on hand washing behaviour on school children in rural India with a significant presence of indigenous tribes. We describe the design choices of our social robot to cater the requirements of the intervention. The custom built wall mounted social robot encouraged 100 children to wash their hand at appropriate time (before meal and after toilet) using the correct handwashing technique via a poster on a wall. The results indicate that the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…2). In our study we found that the influence of the social robot over changing handwashing behaviour was significant (40%) and the students also washed their hands with better technique after the robot intervention [22]. structures between the adult interviewer and the child, including suggestibility.…”
Section: Methodsmentioning
confidence: 57%
“…2). In our study we found that the influence of the social robot over changing handwashing behaviour was significant (40%) and the students also washed their hands with better technique after the robot intervention [22]. structures between the adult interviewer and the child, including suggestibility.…”
Section: Methodsmentioning
confidence: 57%
“…In 2019, researchers from the AMMACHI Labs, Amrita Vishwa Vidyapeetham, conducted a Wizard of Oz experiment among children in a rural Indian school with a social robot called Pepe [25,26]. They leveraged the Hawthorne effect while designing the robot.…”
Section: Building On a Pilot Social Robot Intervention Of Handwashingmentioning
confidence: 99%
“…The children have to know the steps of handwashing in order to perform it. In our previous research studies, we found that rural and semi-urban school children in India do not have the correct knowledge about hand hygiene steps as prescribed by the World Health Organization (WHO) [3]. Therefore, we decided to blend declarative knowledge and procedural knowledge on hand hygiene into a serious game that the children could play with the social robot.…”
Section: A Collaborative Games For Positive Reinforcementmentioning
confidence: 99%